Cu2WS4-CuBi2O4 composite material with photothermal effect as well as preparation method and application of Cu2WS4-CuBi2O4 composite material
By loading Cu2WS4 nanosheets on the surface of CuBi2O4, a Z-type heterojunction of Cu2WS4-CuBi2O4 composite material is formed, which solves the problems of low energy conversion efficiency of photocatalysts and low carrier recombination rate in existing photocatalytic technologies, and achieves efficient photocatalytic degradation effect.
Patent Information
- Application Number
- CN202411680742.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-21
AI Technical Summary
Existing photocatalytic technologies are difficult to effectively utilize infrared light in sunlight, and the catalyst's energy conversion efficiency is low and the carrier recombination rate is not high.
Cu2WS4-CuBi2O4 composite material was used as photocatalyst to prepare rod-shaped CuBi2O4 by hydrothermal method and load Cu2WS4 nanosheets on its surface to form a Z-type heterojunction to enhance the separation efficiency of photogenerated carriers.
It improves photocatalytic activity, improves visible light utilization, enhances the stability and degradation efficiency of the photocatalyst, and can efficiently remove organic pollutants in water.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocatalysis and relates to a Cu2WS4-CuBi2O4 composite material with photothermal effect, a preparation method and application thereof. Background Art
[0002] Since 1911, the concept of photocatalysis first appeared in relevant literature reports. In 1972, scientists Fujishima and Honda observed that hydrogen would be produced on the TiO2 electrode under the irradiation of ultraviolet light. This made people realize that using photocatalytic technology to convert solar energy into chemical energy has become a possible way to solve the current energy shortage and environmental pollution.
[0003] Photocatalytic technology refers to the catalytic reaction and photochemical reaction carried out by photocatalysts under the irradiation of sunlight (ultraviolet light, visible light and even infrared light). It has the advantages of green environmental protection, efficient and thorough degradation of pollutants, simple operation, no secondary pollution and low cost, and has ideal application prospects in the fields of environmental remediation and energy conversion. However, it can usually only use ultraviolet and visible light with high energy and strong penetration in sunlight, and it is very difficult to use infrared light, which accounts for 52% of the total energy of sunlight. In addition, photocatalysis also faces problems such as low catalyst energy conversion efficiency and high carrier recombination rate. Photothermal-assisted photocatalysis is a photocatalytic mode in which thermal energy plays an auxiliary role in the photocatalytic process. In this mode, the photothermal effect of the photothermal material itself is used to increase the surface temperature of the catalyst, enhance the mobility of photogenerated carriers, or increase the mass transfer rate of the reactants, reduce the apparent activation energy of the catalytic reaction, and easily activate the adsorbed active substances, accelerate the chemical reaction kinetics on the catalyst surface, and improve the catalytic reaction activity, becoming an emerging and promising way to solve the current bottleneck of efficient utilization of photocatalysis.
[0004] Based on sulfate radical (SO4 •− ) is a kind of advanced oxidation technology (SR-AOPs) that produces SO4 with super strong oxidation ability. •− Advanced oxidation technology, which uses SO4 as the main active oxygen species, is a pollutant degradation technology that has developed rapidly in recent years. Compared with the hydroxyl radicals (•OH) produced by traditional advanced oxidation technology, SO4 •− With redox potential (E = 2.5-3.1V vs E = 1.8-2.7 V) and a higher half-life (30-40 µs vs 20 ns) and more selective. •− Available through Co 2+ and Cu 2+Transition metal ions such as iodine and iodine activate persulfates including peroxymonosulfate (PMS) and peroxydisulfate (PDS). Activating persulfates effectively promotes SO4 •− , •OH and •O2 - The production of free radicals such as chlorinated carbon dioxide can effectively improve the degradation efficiency of pollutants.
[0005] Copper bismuth oxide (CuBi2O4) is a spinel-structured p-type narrow bandgap semiconductor material (1.6-1.8 eV), with conduction band and valence band potentials of approximately -0.65~-0.63 eV and +1.12~+1.15 eV. It has the advantages of suitable bandgap width, strong visible light response, cheap raw materials, simple synthesis method, and good thermal stability. Rupesh S. Devan prepared CuBi2O4 microspheres assembled from one-dimensional CuBi2O4 nanorods by hydrothermal method, which not only showed excellent absorption in the entire UV and visible spectrum, but also covered the solar spectrum. Xenon light irradiation for 30 minutes can heat water temperature from 28 °C to 38 °C. Thangudu et al. found that CuBi2O4MPs can produce specific photothermal effects under NIR-I (808 nm), NIR-II (980 nm) and NIR-III (1550 nm) light irradiation. Therefore, CuBi2O4 can be used as an ideal photocatalytic material to construct a photothermal assisted photocatalytic system to remove antibiotics. 2+ It can effectively activate PDS, promote the production of active substances in the reaction system, and accelerate the degradation of pollutants.
[0006] Sulfides have narrower band gaps and more negative conduction band values and are considered to be the most promising hot photocatalytic materials in the visible light band. Among them, Cu2WS4, as a p-type semiconductor, has a built-in electric field that promotes electron transfer to the surface, so it usually exhibits superior catalytic activity in pollutant degradation. Despite this, the Cu2WS4 photocatalyst still has the disadvantages of high recombination rate and slow transfer rate of photogenerated carriers. In order to further improve the catalytic activity of the Cu2WS4 photocatalyst, it can be achieved through the synergistic approach of heterostructure construction and photothermal effect. Summary of the invention
[0007] In view of the shortcomings of the prior art, the present invention aims to provide a Cu2WS4-CuBi2O4 composite material with photothermal effect, a preparation method and application thereof. The Cu2WS4-CuBi2O4 composite material with photothermal effect is used as a photocatalyst to activate PDS and promote SO4 •− , •OH and •O2 -The production of active substances such as CuBi2O4 solves the problems of fast recombination of photogenerated carriers and low visible light utilization rate, which can improve its photocatalytic activity and has broader application prospects.
[0008] In order to solve the above technical problems, the present invention adopts the following technical solutions to achieve the above problems: A Cu2WS4-CuBi2O4 composite material with photothermal effect, the composite material is supported by rod-shaped CuBi2O4, and one-dimensional Cu2WS4 nanosheets are loaded on the surface of the rod-shaped CuBi2O4 through interface regulation to form a Z-type Cu2WS4-CuBi2O4 heterojunction with photothermal effect; In terms of mass ratio, the mass ratio of Cu2WS4 to CuBi2O4 is (1-4): (6-9).
[0009] Optionally, in terms of mass ratio, the mass ratio of Cu2WS4 to CuBi2O4 is (2-3): (7-8).
[0010] Optionally, the CuBi2O4 is a rod-like structure with a length of 2 to 4 μm, and the Cu2WS4 is a sheet-like structure with a side length of 1 to 1.5 μm.
[0011] The method for preparing any Cu2WS4-CuBi2O4 composite material with photothermal effect described in the present invention is characterized by comprising the following steps: Step 1, preparing brown-yellow powdered Cu2WS4 by hydrothermal method; Step 2, copper nitrate and bismuth nitrate are added to water and stirred to obtain solution A, and sodium hydroxide is added to solution A and stirred to obtain solution B; Step 3, brown-yellow powdered Cu2WS4 and PEG-4000 are added to solution B, and the precursor C is obtained after stirring and ultrasonication; Step 4, treating the precursor C by a hydrothermal method, cooling, washing and drying to obtain a powdery Cu2WS4-CuBi2O4 composite material with photothermal effect.
[0012] Optionally, the specific process of preparing brown-yellow powdered Cu2WS4 in step 1 is: Cu(NO3)2, Na2WO4 and L-cysteine were added to water in a molar ratio of 2:1:5 and stirred until completely dissolved; kept at 180°C for 24 hours, washed, dried and ground with ethanol and water respectively to obtain brown-yellow powder Cu2WS4.
[0013] Optionally, in step 2, the ratio of copper nitrate, bismuth nitrate and water is 2mmol:4mmol:80mL; The ratio of sodium hydroxide to solution A is 0.8 g:80 mL.
[0014] Optionally, in the step 3, the mass of PEG-4000 is a fixed value of 2 g, and the mass ratio of the brown-yellow powdered Cu2WS4 to the CuBi2O4 in solution B is (1:9), (2:8), (3:7) or (4:6).
[0015] Optionally, the step 4 comprises: adding the precursor C into a high-pressure reactor; reacting at 180° C. for 24 h, cooling to room temperature, washing and drying, and vacuum drying at 70° C. for 12 h to obtain a Cu2WS4-CuBi2O4 composite material.
[0016] Any of the Cu2WS4-CuBi2O4 composite materials with photothermal effect described in the present invention is used for preparing photocatalysts, for photocatalytic reactions and / or for activating persulfate systems.
[0017] Optionally, Cu2WS4-CuBi2O4 with photothermal effect is mixed with water containing organic pollutants, and a photocatalytic reaction is carried out under light conditions to complete the removal of organic pollutants in the water; The ratio of Cu2WS4-CuBi2O4 composite material with photothermal effect to PDS is 20 mg:500 µL, the organic pollutant in the water body containing organic pollutants is tetracycline of the antibiotic class, the photocatalytic reaction temperature is 25 °C, the photocatalytic reaction time is 60 min, the light source used in the photocatalytic reaction is a xenon lamp, and the light intensity of the xenon lamp is 251 mw / cm 2 .
[0018] Compared with the prior art, the present invention has the following technical effects: (1) The Cu2WS4-CuBi2O4 composite material with photothermal effect provided by the present invention is used as a photocatalyst, with rod-shaped CuBi2O4 as a base material, and has excellent physical and chemical properties such as high chemical and thermal stability; further, copper tungsten sulfide (Cu2WS4) is loaded onto the surface of rod-shaped CuBi2O4 to form a composite material, which can inhibit the rapid recombination of photogenerated carriers of CuBi2O4 monomers and Cu2WS4 monomers, improve the utilization rate of visible light, and avoid the agglomeration of Cu2WS4 nanoparticles, thereby ensuring the stability of Cu2WS4, which is beneficial to improving the photocatalytic performance and achieving efficient degradation of organic pollutants.
[0019] (2) The Cu2WS4-CuBi2O4 composite material with photothermal effect of the present invention has enhanced photogenerated electron-hole separation efficiency and high catalytic activity through the Z-type heterojunction formed between Cu2WS4 and CuBi2O4. It also has the advantages of good structural stability and no secondary pollution. As a new type of photocatalytic material, it can improve the actual application efficiency of catalytic materials in the field of degrading organic pollutants in the environment.
[0020] (3) The Cu2WS4-CuBi2O4 composite material with photothermal effect of the present invention further improves the photocatalytic activity of the photocatalyst by optimizing the mass percentage of Cu2WS4. This is because the composite ratio has an important influence on the performance of the photocatalyst. The amount of Cu2WS4 added should be moderate. When the amount of Cu2WS4 added is small, the separation efficiency of photogenerated carriers cannot reach the best; when the amount of Cu2WS4 added is large, the excess Cu2WS4 will accumulate and cover the surface of the composite material, agglomerate and block part of the light beam, reducing the utilization rate of light. The formation of the sea cucumber-like structure and the appropriate composite ratio enable the Cu2WS4-CuBi2O4 composite material with photothermal effect to have more excellent photocatalytic performance.
[0021] (4) The present invention also provides the use of Cu2WS4-CuBi2O4 composite materials with photothermal effect in removing organic pollutants from water. When the photocatalyst is used for photocatalytic degradation of organic pollutants, Cu2WS4-CuBi2O4 accelerates the energy conversion of photogenerated electrons through the photothermal effect and the activation of persulfate by Cu, increases the temperature of the reaction system, promotes the transfer of electrons on the Cu2WS4-CuBi2O4 interface, and accelerates the Z-scheme charge migration mechanism of the heterojunction. On the one hand, it can produce more SO4 •− , •O2 - , ·OH and other active substances can quickly degrade organic pollutants, and on the other hand, it can promote the e - Transfer to the conduction band of CuBi2O4, inhibit the recombination of electron-hole pairs, enhance the photocatalytic activity of the material, and achieve efficient degradation of organic pollutants. The present invention utilizes a Cu2WS4-CuBi2O4 composite photocatalyst with a photothermal effect to activate persulfate to remove organic pollutants in water. The photocatalyst activates persulfate to degrade organic pollutants, and can quickly and efficiently degrade various types of organic pollutants in water. It has the advantages of high safety, simple process, low cost, good removal effect, high efficiency, and no secondary pollution. In particular, it can achieve efficient removal of antibiotics in water, and has extremely high practical application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings: Figure 1 Schematic diagram of the preparation process of the Cu2WS4-CuBi2O4 composite material with photothermal effect prepared in the present invention; Figure 2 XRD diagram of the Cu2WS4-CuBi2O4 composite material with photothermal effect prepared in Examples 1, 2, 3, and 4; Figure 3 The scanning electron microscope image (3a) of CuBi2O4 prepared in Example 3, the scanning electron microscope image (3b) of Cu2WS4, and the scanning electron microscope image (3c) of the 30% Cu2WS4-CuBi2O4 composite material; Figure 4 The photocatalytic degradation diagram (4a) of TC degradation by PDS activated by Cu2WS4-CuBi2O4 with photothermal effect prepared in Examples 1, 2, 3, and 4, the corresponding pseudo-first-order kinetic diagram (4b), the corresponding rate constant diagram (4c), the 4-cycle degradation diagram of TC degradation (4d), the X-ray diffraction diagram (4e) and SEM diagram (4f) of TC degradation reaction before and after 30% Cu2WS4-CuBi2O4 composite material degradation. DETAILED DESCRIPTION
[0023] The present invention will be further described below in conjunction with the accompanying drawings and specific implementation cases. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope limited by the appended claims of the application.
[0024] The present invention provides a Cu2WS4-CuBi2O4 composite material with photothermal effect, a preparation method and an application thereof, wherein rod-shaped CuBi2O4 is used as a supporting material, and the surface of the rod-shaped CuBi2O4 is uniformly distributed with flake Cu2WS4. The preparation method of the composite material comprises: preparing Cu2WS4 powder by a hydrothermal method; adding copper nitrate and bismuth nitrate to deionized water and stirring evenly to obtain solution A, and adding sodium hydroxide to solution A and stirring to obtain solution B; adding Cu2WS4 powder and a fixed mass of PEG-4000 to solution B, stirring and ultrasonicating to obtain a precursor C; treating the precursor C by a hydrothermal method, cooling, washing and drying to obtain a Cu2WS4-CuBi2O4 composite photocatalyst with photothermal effect. The Cu2WS4-CuBi2O4 composite photocatalyst with photothermal effect has good photocatalytic performance and the effect of degrading organic pollutants. The present invention is simple to prepare, has a stable structure, high repeatability, no secondary pollution, and can meet laboratory and industrial needs.
[0025] Combination Figure 1 The method for preparing the Cu2WS4-CuBi2O4 composite photocatalyst having a photothermal effect of the present invention comprises: Step 1. Prepare brown-yellow powdered Cu2WS4 by hydrothermal method; Step 2. Add copper nitrate and bismuth nitrate into deionized water and stir evenly to obtain solution A, and add sodium hydroxide into solution A and stir to obtain solution B.
[0026] Step 3. Add Cu2WS4 powder and PEG-4000 to solution B, stir and ultrasonicate to obtain precursor C; Step 4. Treat the precursor C by a hydrothermal method, and after cooling, washing and drying, obtain powdered Cu2WS4-CuBi2O4 with photothermal effect.
[0027] In the above preparation method, the specific process of preparing Cu2WS4 by hydrothermal method in step 1 is: 2 mmol Cu(NO3)2•3H2O, 1 mmol Na2WO4•2H2O, and 5 mmol L-cysteine were added to 40 mL deionized water and stirred continuously for 1 hour until completely dissolved. The solution was then transferred to a 50 mL autoclave, kept at 180°C for 24 hours, washed several times with ethanol and deionized water, and finally dried in an oven at 70°C. Finally, brown-yellow powder Cu2WS4 was obtained by grinding.
[0028] In the above preparation method, in step 2, the amount of copper nitrate is 2 mmol, the amount of bismuth nitrate is 4 mmol, the volume of deionized water is 80 mL, and solution A is obtained by stirring for 30 min.
[0029] In step 2, 0.8 g of sodium hydroxide was added to 80 mL of solution A and stirred for 30 min to obtain solution B.
[0030] In step 3, the amount of Cu2WS4 powder is 0.089-0.533 g, and the amount of PEG-4000 is 2 g; the stirring time is 30 min, and precursor C is obtained.
[0031] In the above preparation method, step 4 specifically adds the precursor into a 100 mL high pressure reactor; In step 4, the heating temperature of the oven is 180° C., the reaction time is 24 h, and after cooling to room temperature, the product is washed and dried.
[0032] In the above preparation method, the Cu2WS4-CuBi2O4 composite photocatalyst with photothermal effect is finally obtained by drying in a vacuum drying oven at 70°C for 12 h.
[0033] The present invention also provides the use of the above-mentioned Cu2WS4-CuBi2O4 composite material with photothermal effect or the Cu2WS4-CuBi2O4 composite material with photothermal effect obtained by the above-mentioned preparation method for removing organic pollutants in water.
[0034] In the above application, the Cu2WS4-CuBi2O4 composite material with photothermal effect is mixed with water containing organic pollutants, and a photocatalytic reaction is carried out under light conditions to complete the removal of organic pollutants in the water.
[0035] In the above application, the ratio of the Cu2WS4-CuBi2O4 composite material with photothermal effect to the water containing organic pollutants is 0.4g:1L, the organic pollutant in the water containing organic pollutants is the antibiotic tetracycline, and its initial concentration is 40 mg / L. The photocatalytic reaction temperature is 25°C, the photocatalytic reaction time is 60 min, and the light source used in the photocatalytic reaction is a xenon lamp, and the light intensity of the xenon lamp is 251 mw / cm2.
[0036] The following are specific embodiments of the present invention. It should be noted that the present invention is not limited to the following specific embodiments, and any equivalent changes made on the basis of the technical solution of this application fall within the protection scope of the present invention. The difference between the four embodiments is that the mass ratios of Cu2WS4 and CuBi2O4 are different, which are 1:9, 2:8, 3:7 and 4:6 respectively.
[0037] Embodiment 1: The preparation method of the Cu2WS4-CuBi2O4 composite photocatalyst with photothermal effect of this embodiment comprises the following steps: (1) Add 2 mmol Cu(NO3)2•3H2O, 1 mmol Na2WO4•2H2O, and 5 mmol L-cysteine to 40 mL of deionized water and stir continuously for 1 hour until completely dissolved. Then transfer the solution to a 50 mL autoclave, keep it at 180°C for 24 hours, wash it several times with ethanol and deionized water, and finally dry it in an oven at 70°C. Finally, grind it to obtain brown-yellow powder Cu2WS4.
[0038] (2) Weigh 2 mmol of copper nitrate and 4 mmol of bismuth nitrate and dissolve them in a mixed solution of 80 mL of deionized water. Stir the mixture on a constant temperature magnetic stirrer for 30 min to form solution A.
[0039] (3) Add 0.8 g of sodium hydroxide to solution A and stir it on a constant temperature magnetic stirrer for 30 min to form solution B.
[0040] (4) Add 0.089 g of brown-yellow powdered Cu2WS4 and 2 g of PEG-4000 to solution B and stir for 30 min to form solution C.
[0041] (5) Pour solution C into a 100 mL autoclave, heat to 180°C in an oven, and react for 24 h. Wash the obtained product with deionized water and ethanol several times, and dry it in a vacuum oven at 70°C for 12 h. Finally, grind to obtain a powdered Cu2WS4-CuBi2O4 composite photocatalyst with photothermal effect. According to the different addition amounts of Cu2WS4, the sample with an addition amount of 0.089 g is marked as 10%Cu2WS4-CuBi2O4.
[0042] Embodiment 2: The preparation method of the Cu2WS4-CuBi2O4 composite photocatalyst with photothermal effect of this embodiment comprises the following steps: (1) Add 2 mmol Cu(NO3)2•3H2O, 1 mmol Na2WO4•2H2O, and 5 mmol L-cysteine to 40 mL of deionized water and stir continuously for 1 hour until completely dissolved. Then transfer the solution to a 50 mL autoclave, keep it at 180°C for 24 hours, wash it several times with ethanol and deionized water, and finally dry it in an oven at 70°C. Finally, grind it to obtain brown-yellow powder Cu2WS4.
[0043] (2) Weigh 2 mmol of copper nitrate and 4 mmol of bismuth nitrate and dissolve them in a mixed solution of 80 mL of deionized water. Stir the mixture on a constant temperature magnetic stirrer for 30 min to form solution A.
[0044] (3) Add 0.8 g of sodium hydroxide to solution A and stir it on a constant temperature magnetic stirrer for 30 min to form solution B.
[0045] (4) Add 0.2 g of brown-yellow powdered Cu2WS4 and 2 g of PEG-4000 to solution B and stir for 30 min to form solution C.
[0046] (5) Pour solution C into an 80 mL autoclave, heat to 180°C in an oven, and react for 24 h. Wash the product with deionized water and ethanol several times, and dry it in a vacuum oven at 70°C for 12 h. Finally, grind to obtain a powdered Cu2WS4-CuBi2O4 composite photocatalyst with photothermal effect. According to the different addition amounts of Cu2WS4, the sample with an addition amount of 0.2 g is marked as 20%Cu2WS4-CuBi2O4.
[0047] Embodiment 3: The preparation method of the Cu2WS4-CuBi2O4 composite photocatalyst with photothermal effect of this embodiment comprises the following steps: (1) Add 2 mmol Cu(NO3)2•3H2O, 1 mmol Na2WO4•2H2O, and 5 mmol L-cysteine to 40 mL of deionized water and stir continuously for 1 hour until completely dissolved. Then transfer the solution to a 50 mL autoclave, keep it at 180°C for 24 hours, wash it several times with ethanol and deionized water, and finally dry it in an oven at 70°C. Finally, grind it to obtain brown-yellow powder Cu2WS4.
[0048] (2) Weigh 2 mmol of copper nitrate and 4 mmol of bismuth nitrate and dissolve them in a mixed solution of 80 mL of deionized water. Stir the mixture on a constant temperature magnetic stirrer for 30 min to form solution A.
[0049] (3) Add 0.8 g of sodium hydroxide to solution A and stir it on a constant temperature magnetic stirrer for 30 min to form solution B.
[0050] (4) Add 0.343 g of brown-yellow powdered Cu2WS4 and 2 g of PEG-4000 to solution B and stir for 30 min to form solution C.
[0051] (5) Pour solution C into a 100 mL autoclave, heat to 180°C in an oven, and react for 24 h. Wash the obtained product with deionized water and ethanol several times, and dry it in a vacuum oven at 70°C for 12 h. Finally, grind to obtain a powdered Cu2WS4-CuBi2O4 composite photocatalyst with photothermal effect. According to the different addition amounts of Cu2WS4, the sample with an addition amount of 0.343 g is marked as 30%Cu2WS4-CuBi2O4.
[0052] Figure 3 is a scanning electron microscope image of the photocatalyst prepared in Example 3, as shown in Figure 3 (a) and Figure 3 As shown in (b), CuBi2O4 is a rod-like structure with a length of about 2 to 4 μm, and Cu2WS4 is a flake-like structure with a side length of about 1 to 1.5 μm; Figure 3 (c) is a scanning electron microscope image of the Cu2WS4-CuBi2O4 composite photocatalyst with photothermal effect. It can be clearly observed that the flake Cu2WS4 is loaded on the surface of the rod-shaped CuBi2O4, proving that the Cu2WS4-CuBi2O4 composite photocatalyst with photothermal effect was successfully prepared.
[0053] Embodiment 4: The preparation method of the Cu2WS4-CuBi2O4 composite photocatalyst with photothermal effect of this embodiment comprises the following steps: (1) Add 2 mmol Cu(NO3)2•3H2O, 1 mmol Na2WO4•2H2O, and 5 mmol L-cysteine to 40 mL of deionized water and stir continuously for 1 hour until completely dissolved. Then transfer the solution to a 50 mL autoclave, keep it at 180°C for 24 hours, wash it several times with ethanol and deionized water, and finally dry it in an oven at 70°C. Finally, grind it to obtain brown-yellow powder Cu2WS4.
[0054] (2) Weigh 2 mmol of copper nitrate and 4 mmol of bismuth nitrate and dissolve them in a mixed solution of 80 mL of deionized water. Stir the mixture on a constant temperature magnetic stirrer for 30 min to form solution A.
[0055] (3) Add 0.8 g of sodium hydroxide to solution A and stir it on a constant temperature magnetic stirrer for 30 min to form solution B.
[0056] (4) Add 0.533 g of brown-yellow powdered Cu2WS4 and 2 g of PEG-4000 to solution B and stir for 30 min to form solution C.
[0057] (5) Pour solution C into a 100 mL autoclave, heat to 180°C in an oven, and react for 24 h. Wash the obtained product with deionized water and ethanol several times, and dry it in a vacuum oven at 70°C for 12 h. Finally, grind to obtain a powdered Cu2WS4-CuBi2O4 composite photocatalyst with photothermal effect. According to the different addition amounts of Cu2WS4, the sample with an addition amount of 0.533 g is marked as 40% Cu2WS4-CuBi2O4.
[0058] The photocatalytic performance and application test process of the above-mentioned photocatalyst are as follows: The XRD spectra of Cu2WS4, CuBi2O4 and Cu2WS4-CuBi2O4 are shown in Figure 2 As shown, their crystal structure and phase composition are revealed. The diffraction peaks of monomer Cu2WS4 and CuBi2O4 conform to the standard cards PDF#74-3742 and PDF#72-0493, respectively. The diffraction peaks at 36.49°, 42.38°, 61.49°, 73.66° and 77.53° match the lattice planes (111), (200), (220), (311) and (222) of CuBi2O4, respectively. It is worth noting that the diffraction peaks of Cu2WS4 (17.60°, 18.51°, 47.18°, 48.14° and 49.27°) corresponding to the typical lattice planes (002), (101), (220), (105) and (204) are all sharp and strong, indicating that the crystal structure is tetragonal, free of impurities and has high crystallinity. For the Cu2WS4-CuBi2O4 heterojunction, the diffraction peaks of Cu2WS4 and CuBi2O4 were detected, and the main peak intensity of Cu2WS4 at 17.60° and 18.51° gradually increased with the proportion of Cu2WS4 in the Cu2WS4-CuBi2O4 heterojunction, verifying the successful recombination of Cu2WS4 and CuBi2O4.
[0059] The photocatalytic and application performance of the Cu2WS4-CuBi2O4 composite photocatalyst with photothermal effect prepared above and persulfate for synergistic degradation of organic pollutants were measured in a photocatalytic reaction system (CEL-LAB500). A 300W xenon lamp was used as the light source in the reaction system, and the system temperature was kept at about 25°C by circulating cooling water. A 40mg / L tetracycline hydrochloride (TC) solution was used to simulate organic pollutant wastewater, and 20 mg of the above photocatalyst was placed in a 50 mL quartz test tube, and a 40 mg / L TC solution was added at the same time. It was moved to a photocatalytic reactor and magnetically stirred for 30 min in a dark environment to ensure that the above photocatalyst reached adsorption-desorption equilibrium. Add 500 µL of 0.1 mol / L PDS, turn on a 300 W xenon lamp for illumination, take out 3 mL of solution every 10 min, separate it with a centrifuge, extract the supernatant, and measure and record the absorbance of TC with a UV-visible photometer at a wavelength of 357 nm. Then, convert the recorded absorbance into TC concentration through a standard curve, and measure the photocatalytic and application performance of the above photocatalyst.
[0060] like Figure 4 As shown in a, without adding any photocatalyst, TC itself is difficult to degrade, and the removal rate does not exceed 10%. In the photocatalyst + PDS system, after 60 minutes of light reaction, 30% Cu2WS4-CuBi2O4 can degrade 81.2% of TC within 60 minutes, which is 20% and 30% higher than CuBi2O4 and Cu2WS4, respectively. In addition, Figure 4 As shown in b, the photocatalytic degradation of TC by CuBi2O4, Cu2WS4, 10%Cu2WS4-CuBi2O4, 20%Cu2WS4-CuBi2O4, 30%Cu2WS4-CuBi2O4, and 40%Cu2WS4-CuBi2O4 photocatalysts successfully matched the pseudo-first-order reaction kinetics (Langmuir-HinShelwood model). Figure 4 c shows that the rate constant of TC degradation by 30%Cu2WS4-CuBi2O4 (0.02301 min −1 ) are the highest, and pure CuBi2O4 (0.00685 min −1 ) and Cu2WS4 (0.01057min −1 ) are 3.36 and 2.18 times of those in the previous study. This indicates that the prepared Cu2WS4-CuBi2O4 binary composite photocatalyst has good photocatalytic performance in the degradation of organic pollutants system and can effectively remove organic pollutants in water.
[0061] like Figure 4As shown in FIG. d, the 30% Cu2WS4-CuBi2O4 composite photocatalyst prepared in Example 3 still has good photocatalytic degradation performance after repeated recycling, and has excellent stability and recyclability. In addition, Figure 4 e, f are the XRD and SEM images of the 30% Cu2WS4-CuBi2O4 composite photocatalyst prepared in Example 3 before and after use, further illustrating that the composite material has good stability.
[0062] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A Cu2WS4-CuBi2O4 composite material with photothermal effect, characterized in that: The composite material is supported by rod-shaped CuBi2O4. Through interface regulation, one-dimensional Cu2WS4 nanosheets are loaded on the surface of the rod-shaped CuBi2O4, forming a Z-type Cu2WS4-CuBi2O4 heterojunction with photothermal effect. In terms of mass ratio, the mass ratio of Cu2WS4 to CuBi2O4 is (1-4): (6-9).
2. The Cu2WS4-CuBi2O4 composite material with photothermal effect according to claim 1, characterized in that: In terms of mass ratio, the mass ratio of Cu2WS4 to CuBi2O4 is (2-3): (7-8).
3. The Cu2WS4-CuBi2O4 composite material with photothermal effect according to claim 1 or 2, characterized in that: The CuBi2O4 is a rod-like structure with a length of 2 to 4 μm, and the Cu2WS4 is a sheet-like structure with a side length of 1 to 1.5 μm.
4. The method for preparing the Cu2WS4-CuBi2O4 composite material with photothermal effect according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step 1, preparing brown-yellow powdered Cu2WS4 by hydrothermal method; Step 2, copper nitrate and bismuth nitrate are added to water and stirred to obtain solution A, and sodium hydroxide is added to solution A and stirred to obtain solution B; Step 3, brown-yellow powdered Cu2WS4 and PEG-4000 are added to solution B, and the precursor C is obtained after stirring and ultrasonication; Step 4, treating the precursor C by a hydrothermal method, cooling, washing and drying to obtain a powdery Cu2WS4-CuBi2O4 composite material with photothermal effect.
5. The method for preparing the Cu2WS4-CuBi2O4 composite material with photothermal effect according to claim 4, characterized in that: The specific process of preparing brown-yellow powdered Cu2WS4 in step 1 is as follows: Cu(NO3)2, Na2WO4 and L-cysteine were added to water in a molar ratio of 2:1:5 and stirred until completely dissolved; kept at 180°C for 24 hours, washed, dried and ground with ethanol and water respectively to obtain brown-yellow powder Cu2WS4.
6. The method for preparing the Cu2WS4-CuBi2O4 composite material with photothermal effect according to claim 4, characterized in that: In the step 2, the ratio of copper nitrate, bismuth nitrate and water is 2mmol:4mmol:80mL; The ratio of sodium hydroxide to solution A is 0.8 g:80 mL.
7. The method for preparing the Cu2WS4-CuBi2O4 composite material with photothermal effect according to claim 4, characterized in that: In the step 3, the mass of PEG-4000 is a fixed value of 2 g, and the mass ratio of the brown-yellow powdered Cu2WS4 to the CuBi2O4 in solution B is (1:9), (2:8), (3:7) or (4:6).
8. The method for preparing the Cu2WS4-CuBi2O4 composite material with photothermal effect according to claim 4, characterized in that: The step 4 comprises: adding the precursor C into a high pressure reactor; reacting at 180° C. for 24 h, cooling to room temperature, washing and drying, and vacuum drying at 70° C. for 12 h to obtain a Cu2WS4-CuBi2O4 composite material.
9. Use of the Cu2WS4-CuBi2O4 composite material with photothermal effect as claimed in any one of claims 1 to 3 for preparing photocatalysts, for photocatalytic reactions and / or for activating persulfate systems.
10. The use according to claim 9, characterized in that: The Cu2WS4-CuBi2O4 with photothermal effect is mixed with water containing organic pollutants, and a photocatalytic reaction is carried out under light conditions to remove organic pollutants in the water. The ratio of Cu2WS4-CuBi2O4 composite material with photothermal effect to PDS is 20 mg:500 µL, the organic pollutant in the water body containing organic pollutants is tetracycline of antibiotics, the photocatalytic reaction temperature is 25 °C, the photocatalytic reaction time is 60 min, the light source used in the photocatalytic reaction is a xenon lamp, and the light intensity of the xenon lamp is 251 mw / cm 2 .
Citation Information
Cited By
Cs3Bi2Br9 / Cu2WS4 heterojunction photocatalyst and preparation method and application thereof
CN122517061A
A Cs3Bi2Br9 / Cu2WS4 heterojunction photocatalyst, its preparation method and application
CN122517061B